The Structure of the Upper Mantle Transition Zone Beneath Northeast China Associated With Mantle Plume Migration - Chuansong He (Earth and Space Science, 2021)
Abstract The stagnation and dehydration of the Pacific Plate slab in the mantle transition zone (MTZ) are widely accepted to have resulted in Mesozoic and Cenozoic volcanic activities and the formation of the Songliao Basin in NE China. However, this notion has been challenged by recent seismic studies. Alternatively, a mantle plume may have generated the large‐scale volcanism and may have led to the formation of the Songliao Basin. In this study, a detailed analysis involving common conversion point stacking of receiver functions was carried out. The results reveal a significantly deepened region of the 410 km discontinuity and an elevated region of the 660 km discontinuity in the center of NE China (specifically, the Songliao Basin). The combination of these results with those of a previous study suggests that an upwelling mantle plume was located under the Songliao Basin in the Mesozoic. Furthermore, the distinctive structure of the MTZ beneath the southern part of the Songliao Basin identified in this study corresponds to mantle plume upwelling (a mushroom‐shaped low‐velocity anomaly), which may be related to the Changbaishan volcanic activity in the Cenozoic.